Panvascular medicine: integrated clinical management ; with 291 tables - Lanzer, Peter 1950-; Topol, Eric J. (Springer Berlin Heidelberg Imprint: Springer, 2002)
The textbook is designed to provide an interdisciplinary and integrated perspective of modern vascular cure. Written by experts the text proceeds from fundamental principles quickly to advanced concepts thus allowing an easy access to the junior practitioner as well as to the seasoned expert in the field